2020
DOI: 10.3390/ijms22010380
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Profiling of the First Human Dental Pulp Mesenchymal Stem/Stromal Cells from Carbonic Anhydrase II Deficiency Osteopetrosis Patients

Abstract: Osteopetrosis is a hereditary disorder characterized by sclerotic, thick, weak, and brittle bone. The biological behavior of mesenchymal cells obtained from osteopetrosis patients has not been well-studied. Isolated mesenchymal stem/stromal cells from dental pulp (DP-MSSCs) of recently extracted deciduous teeth from osteopetrosis (OP) patients and healthy controls (HCs) were compared. We evaluated whether the dental pulp of OP patients has a population of MSSCs with similar multilineage differentiation capabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…We previously reported that the dental pulp of OP patients contains a population of mesenchymal stem/stromal cells (MSSCs) capable of multilineage differentiation comparable to that of healthy subjects’ DP-MSSCs [ 8 ]. Our isolated DP-MSSCs were shown to be CD44-, CD73-, CD105- and CD90-positive by immunohistochemistry and flow cytometry analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously reported that the dental pulp of OP patients contains a population of mesenchymal stem/stromal cells (MSSCs) capable of multilineage differentiation comparable to that of healthy subjects’ DP-MSSCs [ 8 ]. Our isolated DP-MSSCs were shown to be CD44-, CD73-, CD105- and CD90-positive by immunohistochemistry and flow cytometry analysis.…”
Section: Discussionmentioning
confidence: 99%
“…High bone density on radiographs is a common symptom of this condition, first recognized in 1904 by the German radiologist Albers-Schonberg [ 7 ]. This most noticeable sign of increased bone density on radiographs is caused by low osteoclast activity, which reduces bone resorption [ 8 , 9 ]. Instead of conferring strength, the overly dense bone architecture leads to brittleness, which predisposes to fracture and subsequent infections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complex proteomic data were generated between the sample groups as previously described. 16,22 The MS data were acquired in an m/z range of 50-2000 Da with a gradient acquisition run time of 120 min using ion-mobility separation experiments (HDMS E ). Each sample was analyzed in triplicate runs using the Mass Lynx platform (Version.…”
Section: Protein Identificationmentioning
confidence: 99%
“…They are usually obtained from the permanent teeth of adults [14], and also from the tissue of dead teeth or lesions (such as periodontitis, root resorption, pericoronitis, and osteopetrosis) [15][16][17]. Research has shown that dental pulp stem cells (DPSCs) in the inflamed dental pulp and DPSCs from inherited dental diseases were not damaged by the disease environment and had similar stem cell properties and immunosuppressive effects to healthy DPSCs [17][18][19]. DPSCs have MSCs properties and have the potential to differentiate into osteoblasts, adipocytes, and neuronal cells [20].…”
Section: Introductionmentioning
confidence: 99%